2002
DOI: 10.1021/jo0159800
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis and Estimation of the Conformational Flexibility of 6-Oxoperhydropyridazine-3-carboxylic Acid Derivatives

Abstract: alpha,beta-Didehydroglutamates have been diastereoselectively transformed into 6-oxoperhydropyridazine-3-carboxylic acid derivatives (OPCAs), which constitute a new class of cyclic amino acid derivatives. Acylation at N-1 renders dipeptides which show considerable conformational rigidity. Semiempirical calculations suggest that OPCAs might force peptide turns with different amplitudes depending on the substitution pattern and relative stereochemistry of the substituents of the pyridazinone ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The obtained dihydropyridazone 3a was enolized and reacted with iodomethane to give the corresponding α-methyl dihydropyridazone 6 in 82% yield with exclusive diastereoselectivity and without erosion of enantioselectivity (Scheme 3). 18 A plausible catalytic cycle is depicted in Scheme…”
Section: Resultsmentioning
confidence: 99%
“…The obtained dihydropyridazone 3a was enolized and reacted with iodomethane to give the corresponding α-methyl dihydropyridazone 6 in 82% yield with exclusive diastereoselectivity and without erosion of enantioselectivity (Scheme 3). 18 A plausible catalytic cycle is depicted in Scheme…”
Section: Resultsmentioning
confidence: 99%
“…The title compound was prepared according to the above general procedure from tert -butyl 6-oxo-4,5-dihydropyridazine-3-carboxylate (650 mg, 3.28 mmol, 1 equiv) and NaBH 3 CN (412.2 mg, 6.6 mmol, 2 equiv) in MeOH (16.4 mL, 0.2 M) in 4 h. Flash column chromatography over silica gel (CH 2 Cl 2 /MeOH 97:3 v/v) afforded the title compound as a white powder (353 mg, 54%). mp 109–110 °C.…”
Section: Methodsmentioning
confidence: 99%
“…As ar esult, the cyclization of 3a proceeded smoothly,i nD CE at 70 8 8C, by an isomerization/intramolecular aza-Michael sequence to give 3-(p-tolyamino)-5,6-dihydropyridazin-4(1H)-one (8a)i n6 5% yield after 12 hours.Similarly,the N-aryl 3-amino-5,6-dihydropyridazinone derivatives 8d, 8e,a nd 8g-i were also obtained in good to high yields. [16] To understand the mechanisms for the formation of 3, control experiments were carried out. Theproduct 3n was produced in 80 %y ield when the reaction of 1n with 2a was carried out under an itrogen atmosphere.I nc omparison, no reaction was observed by treating (E)-1-phenyl-2-(p-tolylimino)ethanone with 2a under identical reaction conditions.T hese results indicate that (E)-1-phenyl-2-(ptolylimino)ethanone,w hich could be formed by aerobic oxidation of 1n in the presence of ab ase,i snot involved for the formation of 3n.Furthermore,the 1 HNMR studies of the reaction of a-diazocarbonyls with as eries of bases were conducted to gain information for the formation of 3.T esting the mixture of 2a with either DBU,D BN,D ABCO,o r triethylamine (TEA) at room temperature showed that: 1) the mixture of 2a with TEA or DABCO gave nothing…”
Section: Methodsmentioning
confidence: 99%